Provide early desertification warning system based on climate and groundwater criteria (Study area: Aq Qala and Gomishan counties) - abdolhossien boali; hamidreza asgari; Ali Mohammadian Behbahani; Abdolrassoul Salmanmahiny; babak naimi (جغرافیا و توسعه, 2021)
In this research, the desertification process is evaluated using 3 climate indicators and 4 groundwater indices in the form of a modal model in a period of 20 years (2008-2017) in the west of Golestan province with the aim of providing a desertification warning system.Then, by determining the threshold limits for the influential indicators in the desertification process of the region, the desertification early warning system was presented based on four indicators. The results of the index change the trend showed that drought indices, total soluble materials, electrical conductivity, and groundwater depth had the greatest impact on desertification in the region, respectively. Desertification warning maps have shown an increase in drought indicators, total solubility, and electrical conductivity from west to east. Also, the groundwater depth index in the central areas has the highest warning range. According to the results obtained from monitoring desertification indicators, the electrical conductivity index during the years 1999, 2001, 2004 to 2006 and 2009, the Total dissolved solids index in the years 1998, 1999, 2001, 2004, 2006 and 2007, Groundwater depth index of 2001, 2002, 2006, 2008 and 2014, Finally, the drought index is in the warning range during the years 1999 to 2003, 2006 to 2008, 2011, 2014, 2015 and 2016. Irrigated lands, drylands and wetlands in the East region affected by desertification warning have been that on this basis is suggested for better management of the land, the threshold defined in this study as the basis for the work to be placed.